Effect of Photoblastism on Rice Morphogenesis and Seedling Development - Hoque, MN; Islam, MA; Islam, MZ; Rahman, M; Biswas, B (Journal of Environmental Science and Natural Resources, 2022)
The effect of continuous light and complete dark period on seed germination to first leaf emergence was examined in BRRIdhan71 and BRRIdhan81 in controlled environment at 22 ± 2 ᵒC and 82± 2 % of relative humidity, with or without supplemental LED white light. In the dark, BRRIdhan71 had a germination rate of 97 percent and BRRIdhan81 had a germination rate of 57 percent. Germination was 92 percent in BRRIdhan81 and 77 percent in BRRIdhan71 under photoblastic conditions (Light). The dark and light treatments had a noticeable impact on the percentage of seeds that germinated. Coleoptile was longer in dark than light in BRRIdhan71. In both rice varieties, the light and dark treatments had little effect on the first leaf length, although the first leaf breadth increased noticeably in BRRIdhan81. The growth condition had an impact on root length, seedling fresh weight, and dry weight. Germination percent, coleoptile length, prophyll length, first leaf length, and root length all decreased in BRRIdhan71, whereas germination percent, first leaf length, first leaf breadth, seedling freash, and dry weight all increased significantly in BRRIdhan81.The findings imply that BRRIdhan71 and BRRIdhan81, in particular, responded to photoblastic treatment and predominantly possess photoblastic biocomponents in seed, which affect germination and subsequent growth phases. Rice seed during germinate in the field will light stress if photoblastism is not considered during the development and release of rice varieties for different seasons, such as Aman and Boro, because light affects seeding photomorphogenesis differently in different growth environments. Environ. Sci. & Natural Resources, 13(1&2): 43-49, 2020